MEWUJUDKAN DESA INOVASI TEKNOLOGI MELALUI PENGGUNAAN KOMPOSIT (RESIN DAN SERBUK LIMBAH BAWANG) DI DESA BANGSRI DAN DESA PESANTUNAN KABUPATEN BREBES - Santoso, Irfan; Farid, Ahmad; Kusuma, Mobinta (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
TThe area of harvested shallots in Brebes is 60.82% of the total harvested area in Central Java Province. Production of shallots in 2018 reached 10,519,484 quintals. Pesantunan Village, Wanasari District, has a high productivity of 121.544 quintals/Ha and Bangsri Village has a productivity of 98.28 quintals/Ha. The abundant potential of onions also has an impact on the abundant onion waste, so that the potential for this onion waste will be made a composite as the embodiment of the Innovation Village. The purpose of this community service activity is to create a Technology Innovation Village to community groups in Pesantunan and Bangsri Villages regarding the use of onion waste into a composite.The method offered is divided into two, namely Soft Program and Hard Program.The result of the composite technology innovation village program, number of participants in the Pesantunan Village was 25 from the "Santun Asri" community group and 15 people in the Bangsri Village from the "Bumdes" membership. Participants were provided with a soft program including waste management and technology innovation villages in the composite field. Participants were also provided with a Hard Program, is practicing making composites with waste onions